BTL: A Framework for Measuring and Modeling Energy in Memory Hierarchies - Manousakis, Ioannis; Nikolopoulos, Dimitrios S. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
Understanding the energy efficiency of computing systems is paramount. Although processors remain dominant energy consumers and the focal target of energy-aware optimization in computing systems, the memory subsystem dissipates substantial amounts of power, which at high densities may exceed50% of total system power. The failure of DRAM to keep up with increasing processor speeds, creates a two-pronged bottleneck for overall system energy efficiency. This paper presents a high-performance, autonomic power instrumentation setup to measure energy consumption in computing systems and accurately attribute energy to processors and components of the memory hierarchy. We provide a set of carefully engineered micro benchmarks that reveal the energy efficiency under different memory access patterns and stress the importance of minimizing costly data transfers that involve multiple levels of the system's memory hierarchy. Lastly, we present BTL (Bottom line), a processor specific model for deriving lower bounds of energy consumption. BTL predicts the minimum dynamic energy consumption for any workload, thus uncovering opportunities for energy optimization.